Light intensity and spectral composition drive reproductive success in the marine benthic diatom Seminavis robusta - Gust Bilcke (Scientific Reports, 2021)
Abstract The properties of incident light play a crucial role in the mating process of diatoms, a group of ecologically important microalgae. While species-specific requirements for light intensity and photoperiod have been observed in several diatom species, little is known about the light spectrum that allows sexual reproduction. Here, we study the effects of spectral properties and light intensity on the initiation and progression of sexual reproduction in the model benthic diatom Seminavis robusta. We found that distinct stages of the mating process have different requirements for light. Vigorous mating pair formation occurred under a broad range of light intensities, ranging from 10 to 81 µE m−2 s−1, while gametogenesis and subsequent stages were strongly affected by moderate light intensities of 27 µE m−2 s−1 and up. In addition, light of blue or blue–green wavelengths was required for the formation of mating pairs. Combining flow cytometric analysis with expression profiling of the diatom-specific cyclin dsCyc2 suggests that progression through a blue light-dependent checkpoint in the G1 cell cycle phase is essential for induction of sexual reproduction. Taken together, we expand the current model of mating in benthic pennate diatoms, which relies on the interplay between light, cell cycle and sex pheromone signaling.